O empreendedorismo em uma cadeia produtiva de leite: desenvolvimento de uma medida - Soares, Júlio Cesar Valandro (2011)
The central objective of this doctorate thesis is establish inferences about possible correlations between entrepreneurial characteristics of rural properties managers which are inserted in the context of a dairy supply chain and its respective rural properties performance, taking as reference an measure proposed evaluation (structured) and validated for this context. This proposal sprang up from a gap in terms of research, identified in literature that deals with themes bound by supply chains and, especially, e, by the entrepreneurial. Thus, a research instrument was structured from several steps, taking as main references the entrepreneurial literature itself, especially the McClelland approach, specialists opinions that deal themes of this thesis and the pre-test experience realized with a non-probabilistic sample of rural producers included in the supply chain object of this research. On the other hand, to identify the researched rural properties performance it was sought, with a south-east of Goiás-Brasil cooperative (COACAL) data bases, statistics regarding milk deliveries from producers associated with the respective cooperative, besides COACAL itself characteristic information and of the dairy segment of Brazil s central west, of primary and secondary resources. With these data, descriptive, qualitative and quantitative analyses about the studied supply chain and the dairy segment of Brazil s central west were done, besides the aspects regarding the data collecting process experience, from the researcher s team reports. Analyses looking for to validate the measure proposed in this thesis were realized basing some statistic procedures like exploratory factor analyze, Mann Whitney s test and multiple linear regression analyze. Finally, it s possible to conclude that the measure structured by this thesis showed evidences about its capacity to stablish relationships between rural properties managers entrepreneurial characteristics and the respective rural properties performance, and to demonstrate that these relationships are effectively valid.